'Ulam' : Consumption Amongst Kelantanese Malay From Selected Districts And Their Antioxidant Properties - Alias, Nur Nadzifah Che (2011)
Eating styles have been shown to exert a major impact on the quality of life and this can be shown in the health status of the individuals. So the saying ‗We are what we eat‘. The present study was carried out to evaluate the consumption of ‗ulam‘ amongst Kelantanese Malay who were synonyms with the famous Kelantanese cuisine of nasi kerabu and nasi ulam. 168 participants, 67 male and 101 female had agreed to participate in this survey. They were residents from the districts of Batu Mengkebang, Salor and Tawang, aged 18 years old and above. The result showed 32.8% of male and 32.7% of female participants took ‗ulam‘ daily.